INDONESIAN KENAF FIBER EXPORT POTENTIAL AS A RAW MATERIAL FOR VARIOUS INDUSTRY - Maria Widyastuti; Lusy Lusy; Ignatius Reynald (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research is a qualitative descriptive study which aims to explore the kenaf fiber. From secondary data and interviews conducted with the Center for Fiber and Sweetener Plants (Balittas). Kenaf fiber from stems is the mainstay of exports. Indonesia has been exporting kenaf to Japan since 2010. The material being exported is Sterilized Kenaf Core Dry Kenaf. Even though kenaf is a plant commodity, the health certificate issued by the Agricultural Quarantine is a Health Certificate/HC. Based on data from the IQFAST automation system in the Surabaya Agricultural Quarantine work area, kenaf exports in 2019 until the first week of August were 76 tons or equivalent to Rp. 554 million. This has reached 88.8% of total exports in 2018 which reached 85.5 tons. According to IQFAST data, the export of Sterilized Kenaf Core Dry Kenaf during the first half of 2020 has been carried out 2 times with a total volume of 13,080 tons worth more than Rp. 9.53 billion rupiah to Japan Keywords: export, kenaf, raw materials, various industries